Annual litterfall Production in the Medium-high Tides Mangrove Area of Angke Kapuk Protected Forest - Amandita Lintang Rumondang; Cecep Kusmana; Sri Wilarso Budi (Journal of Natural Resources and Environmental Management)
Litterfall production in the mangrove ecosystem is essential for the mangrove community. It also has an essential role in contributing carbon to estuaries in the tropics. This study aimed to determine the mangrove litterfall production in the Angke Kapuk Protected Forest area, Indonesia, which has a medium-high tide tidal type, and how environmental factors affect the litterfall production. The method used to catch litterfall in the forest for a certain period was the litter-trap method with 34 litter-traps size 1 × 1 meter each and a mesh size of 1 mm spread out systematically and suspended above the maximum tidal height. The trapped litterfall was sorted into leaves, twigs, and reproductive components. Litterfall was baked in an oven at 105 oC for 24 hours, and the dry weight was weighed. The annual production of mangrove litterfall in the medium-high tides area is 761.37 g m2. Leaves were the most dominant component of mangrove litterfall. There is no significant correlation between litterfall production and monthly rainfall, while the correlation between litterfall production and wind speed only affects reproductive parts significantly affected by wind speed.